Effects of Different Level of Sawdust Substrates on the Growth and Yield of Oyster Mushroom (Pleurotusostreatus) - Chanthan Or; Putheasath Sin; Chhun Hong; Vanchey Ros; Tithya Kang; Saroeun Kong; Dina Pen; Mardy Serey (Techno Agriculturae Studium of Research, 2024)
The objective of the experiment was to test the effect of different levels of sawdust substrates on the growths and yields of oyster mushroom. The experimental design was a Randomized Complete Block Design (RCBD) involved five treatments and four replications. The treatments were T1: rice husk 70% plus other substrate, T2: rice husk 80% plus other substrate, T3: rice husk 90% plus other substrate, T4: rice husk 80% plus other substrate and T5: rice husk 100% plus with other substrate. A total of 500 bags were representatives for 5 treatments or 100 bags for 4 replications or 25 bags for one replication. Three randomize mushroom bags among 25 bags in each replications were representative samples to measurement. Though the experiment shows that length, cap diameter, number of fruit body/packet, yield/packet and total yield in 25 bags were not significant different (P>0.05) among different treatments but total yield was better when sawdust used at 80%and substrates from rice husk (25%), rice straw (5%), rice bran (5%) and other element substrates.